AMERICAN LITERARY REALISM AND NATURALISM - Jumanazarova Nilufar Ilhom qizi; Khamitov Eldorbek Erkin o’g’li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Literary trends that mirrored the shifting social and environmental conditions of the era included Naturalism and American Literary Realism in the late 19th and early 20th centuries. With an emphasis on the harsh facts of society, nature, and human existence, realism and naturalism in American literature sought to depict reality as it actually was, free of romanticism or idealization. Important literary trends that arose in the late 19th and early 20th centuries were Naturalism and American Literary Realism, which represented a tendency toward presenting life as simply as possible. The goals of these movements were to portray the difficulties faced by society, the intricacies of human existence, and the impact of environment on people.